Analysis of the correlation between laboratory results and flatwater test reached by Spanish elite paddlers - Garcia-Soidan, J. L.; Garcia Soidan, P.; Huelin Trillo, F.; Garcia Allegue, C.; Barcala Furelos, R. (Archivos de medicina del deporte, 2008)
Introduction: The aim of this work was to determine the relationship existing between the lab-measured variables and fl atwater test results in elite paddlers. With this purpose, a research was carried out with the participation of six top paddlers belonging to the national team. Material and methods: In two time periods, kayakergometer tests and other lab analysis were applied to these athletes, and besides, with a margin of 15 days of difference each time, fl atwater tests, in a 1000m lane, were carried out. Results and conclusions: In order to make an initial evaluation of the relationship between lab-measured variables and course times, we obtained the total correlations or those data presenting a value of regarding time variable. The main conclusions of this study can be summed up into two ideas: the identifi cation of a set of independent variables which signifi cantly explains the variability in times reached by paddlers: the average VO2 and the average W. On the other hand, the possibility to establish a valid adjustment, in this case a linear one, which makes possible to quantify the related rates among signifi cant variables, as well as how to foresee future time results of athletes having into account present lab and fl atwater test data: VR Foreseen Time = -0.757 + 0,009* VR VO2med + 0,037 * VR Wmed.